The Relationship Between Internal Marketing, Job Satisfaction, Organizational Commitment, And Market Orientation: A Study On Manufacturing Companies In Northern Region Of Malaysia - Cheah, Phaik Lean (2005)

(untitled)
Kepentingan pemasaran dalaman menjadi tumpuan kebanyakan organisasi, terutama dalam bidang perkhidmatan.